2008
DOI: 10.1089/ars.2007.1968
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Expression of the Antioxidant Heme Oxygenase-1 in Primary Cells and Tumor Cells: Regulation by Interaction of USF-2 and Fra-1

Abstract: Heme oxygenase-1 is the rate-limiting enzyme for the degradation of the prooxidant heme. Previously, we showed that an E-box within the HO-1 promoter is crucial for the regulation of HO-1 expression in primary hepatocytes. Further to investigate the importance of this E-box, we determined the regulatory capacity of the E-box-binding factor USF-2 in primary cells in comparison with transformed cell lines. We found that HO-1 expression was inhibited by USF-2 in primary cells, whereas it was induced in tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
2
11
0
Order By: Relevance
“…This data suggests that inducing HO-1 levels increases cellular viability and, thus, confers protection to SH-SY5Y cells. Our results are in agreement with earlier reports wherein induction of HO-1 in cells has been shown to confer protection to cells against oxidative stress [35,36,37]. …”
Section: Discussionsupporting
confidence: 94%
“…This data suggests that inducing HO-1 levels increases cellular viability and, thus, confers protection to SH-SY5Y cells. Our results are in agreement with earlier reports wherein induction of HO-1 in cells has been shown to confer protection to cells against oxidative stress [35,36,37]. …”
Section: Discussionsupporting
confidence: 94%
“…Our present data indicates that the anti-inflammatory effects of ATR-I are, at least in part, due to the inhibition of ROS and the induction of antioxidant enzymes (HO-1 and MnSOD). Our results are also in agreement with previous works, wherein the induction of HO-1 facilitates cellular protection against NO-induced injury [69,70] and MPTP-induced oxidative stress [71,72,73]. …”
Section: Discussionsupporting
confidence: 93%
“…This is an important mechanism underlying the neuroprotective effects of HO-1 and NRF2, proposed by several in vitro and in vivo studies. Studies have shown that up-regulation of HO-1 expression and the subsequent increase in HO activity may confer an adaptive neuroprotective response to oxidative insults both in vitro and in vivo , mediated by the activation of NRF2 [29,30]. Indeed, in a study using the acute MPTP model, it was shown that NRF2−/− mice are more sensitive to MPTP [31].…”
Section: Discussionmentioning
confidence: 99%